Aesthetic Morphological Study of Zero Waste Pattern in Men’s Shirt Design - Simamora M, Regina; Nursari, Faradillah; Larissa, Tiara; Yuningsih, Sari (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Aesthetic morphology studies can be carried out on men's shirt fashion design using the Zero Waste Pattern technique as one of the more varied men's shirt model design ideas. The study of Aesthetic Morphology by Thomas Munro is a study through the description, comparison, and analysis of the structure of the shape of an art object scientifically and systematically on the elements of art, design principles, and expressions resulting from the elements that form an art object. The purpose of this study is to examine the Aesthetic Morphology of men's shirt design using the Zero Waste Pattern technique, so as to find a shirt design whose product can be visualized and in accordance with aesthetic principles. The method used in this study is qualitative descriptive, the purpose is to understand the study of Aesthetic Morphology with research practices that emphasize exploratory aesthetics to describe the visual form, style, and visual expression of men's shirt design using the Zero Waste Pattern technique. The results of creative exploration resulted in 2 men's shirt designs, one of which is a Fit To Body design with a Casual Style with fabric waste of 2.1% and a Regular Fit Men's Shirt design with a Retro Style with fabric waste of 1.7%. The results of the study found that the 5 main criteria for designing using the Zero Waste Pattern technique, namely Aesthetics, Comfort, Cost, Sustainability, and Manufacturability, are known to consider psychological and sociology factors of art. A study using description, comparison, and analysis on the Zero Waste Pattern technique can find a men's shirt design line that is more varied, practical, supports sustainable trends, and is in accordance with aesthetic principles.